An Exegetical and Cultural Examination of “Shi er you ze xue, xue er you ze shi仕而优则学，学而优则仕” - Lian, Yanting (International Journal of Culture and History, 2024)
“Shi er you ze xue, xue er you ze shi 仕而优则学，学而优则仕(An official versed in state affairs should amplify his knowledge; an intellectual well equipped with knowledge should serve the state.)” was put forward by Confucian scholars during the Spring and Autumn Period in the light of the social reality that many people had not yet learned to serve, but its connotation was often misinterpreted by later generations as “the theory of studying to become a government official”. Examined from an exegetical and cultural point of view, it can be seen that “xue学” refers to the study of moral and etiquette norms and knowledge of literature, and “you优” means “abundance, spare capacity”. “shi仕” refers to being an official; ‘Shi er you ze xue仕而优则学’ is a compromise way adopted by Confucianism to solve the contradiction between ideals and reality; ‘xue er you学而优’ is the prerequisite for ‘shi仕’; and ‘shi仕’ is a bridge for Confucianism to realize the ideal of helping the world.